2020
DOI: 10.1016/j.envpol.2020.115488
|View full text |Cite
|
Sign up to set email alerts
|

A review of organic waste enrichment for inducing palatability of black soldier fly larvae: Wastes to valuable resources

Abstract: The increase of annual organic wastes generated worldwide has become a major problem for many countries since the mismanagement could bring about negative effects on the environment besides, being costly for an innocuous disposal. Recently, insect larvae have been investigated to valorize organic wastes. This entomoremediation approach is rising from the ability of the insect larvae to convert organic wastes into its biomass via assimilation process as catapulted by the natural demand to complete its lifecycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 122 publications
0
43
0
2
Order By: Relevance
“…This LCA publication was cited with respect to the site selection for landfills [153,154] and in a study which yielded the controversial statement that "recycling metals except gold had more negative environmental impacts than mining" [155]. Further citing studies deal with environmental impacts of combustion-based energy production [156], composting on closed landfill sites [157], bioreactor landfills [158], suppression of methane generation [159], modelling of landfill gas production [160], organic waste enrichment [161]. Within NEW-MINE, LCA was also applied to compare smelting of MSWI bottom ash with the state-of-the-art mineral process-ing approach and revealed that the energy demand for smelting processes overrules, with respect to global warming, the positive effect of secondary raw material production [162].…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…This LCA publication was cited with respect to the site selection for landfills [153,154] and in a study which yielded the controversial statement that "recycling metals except gold had more negative environmental impacts than mining" [155]. Further citing studies deal with environmental impacts of combustion-based energy production [156], composting on closed landfill sites [157], bioreactor landfills [158], suppression of methane generation [159], modelling of landfill gas production [160], organic waste enrichment [161]. Within NEW-MINE, LCA was also applied to compare smelting of MSWI bottom ash with the state-of-the-art mineral process-ing approach and revealed that the energy demand for smelting processes overrules, with respect to global warming, the positive effect of secondary raw material production [162].…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…While beneficial, the potential of H. illucens is not without challenges, and a summary of these are shown in Table 1.3 The economical scale of technologies [13,14,29] where the supply chains for the input of waste and distribution of extracted products and frass for various industries are still lacking. For example, the processing to animal feed and the frass to be sent to nearby farms and agricultural land may be a logistic challenge.…”
Section: Challenges In Implementation Of Hermatia Illucens Biowaste Treatmentmentioning
confidence: 99%
“…An upcoming solution for organic waste, the H. illucens larvae have been gaining interest worldwide as a more acceptable food waste solution and in generating valuable biomass for the circular economy [12][13][14]. As a 13-20 mm long fly in the insect family Stratiomyidae native to the Neotropics but found across all zoogeographic regions due to anthropogenic factors, H. illucens can be bred all year round in the tropics and in warmer months in colder areas [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Kemampuan fungi mendegradasi aneka substrat di alam dalam kelangsungan hidupnya memiliki potensi sebagai agen yang dapat memanfaatkan limbah organik untuk sumber nutrisi (Ahuja et al, 2020;Jain and Kalamdhad, 2020;Raksasat et al, 2020;Thaha et al, 2020). Suatu limbah organik yang belum dimanfaatkan dan masih mengandung unsur-unsur nutrisi terutama N dan zat perangsang tumbuh (auxin dan sitokoni) dapat menjadi substrat untuk pertumbuhan fungi adalah limbah cair tempe dan air kelapa.…”
Section: Pendahuluanunclassified